(untitled) (KASBIT Business Journal, 2017)
The impact of capital structure on the financial performance of firm is the key purpose of this study by using a sample of 60 firms of textile industry in Pakistan for the period of 2010-2014. Panel data procedure is used for the measurement of firm’s financial performance. ROA and ROE are depended variables and assets turn over, growth, debt to assets, and debt to equity, total debt ratios, short term debt and long term debt as in-depended variables who lead to capital structure. As well as, firm size as control variable and panel data regression technique is used. ROA and ROE have significant positive relationship with debt to equity and debt to asset. As well as, in sample companies of Pakistan textile industry we found significant positive relationship among performance and growth; ROA and firm size; ROA, ROE and short term debt; long term debt and ROA; total debt and performance of the firm analysis. However, there is negative relationship exist between ROE and firm size; ROE and Long term debt. All the results of correlation matrix, regression model, and descriptive analysis indicate the same results that if a company manages the appropriate capital structure it can increases the financial performance of the corporations. Also, results indicate that manager can improve the textile sector financial performance. To conclude, finding of our study helps to support the arguments of trade-off theory that firms should use more debt incorporate in the capital structure and this help to improve the performance of the organization.